From Grassroots to Success: A Case Study of a Successful Goan Woman Entrepreneur - Costa, Juao C.; Shah, Harshal; Korgaonkar, Kapil (Prabandhan: Indian Journal of Management, 2015)
Goa - The Pearl of the East on the world map, flaunts its serene and beautiful beaches and ancient Portuguese architecture that attracts an influx of tourists and boosts the economy. Besides this, Goa, the twenty fifth state of federal India, is famous for its own authentic and unique cuisine and sea-food. More specifically, we find an increasing number of tourists looking out for authentic Goan cuisine. One of the success stories worth mentioning is of an entrepreneuring widow from Betalbatim, South Goa who stood against the tide, stuck to her grass roots, and proved her abilities in providing authentic Goan dishes. Martin's Corner was established in 1989 by the Late Mr. Martin Pereira as a corner shop where local village boys would come to play carom or to grab a soft drink. Mrs.Carafina, the wife of Late Mr. Martin Pereira along with her dedicated sons, started serving popular Goan dishes, which instantly became famous among the Goans for her exquisite cooking. In no time, her delicacies became popular not only in Goa, but outside Goa too. Today, it has grown to become one of Goa's most talked about and most frequented multi-cuisine restaurants for authentic Goan and fresh sea food. It has been patronized by many Bollywood film stars, top cricketers, politicians, corporates, foreign tourists, and not to forget, Goans from all walks of life. Also noteworthy is their ability to serve both vegetarian and non-vegetarian clientele. Every scrumptious meal in the evening at Martin's Corner is accompanied with live entertainment. The ambience portraying Goan culture, casual, and easy atmosphere leaves you with a feeling of contentment. What is the secret behind the success of Mrs. Pereira's (who has not learned the ropes of management from a B-school) entrepreneurial venture? How did she manage to market her small corner shop to become a popular food stop for many rich and famous personalities as well as middle class people? The present case study explores the journey of Martin's Corner from a small corner shop to one of the most popular and loved restaurants in Goa.